Analysis of histologic follow‐up and risk of malignancy for salivary gland neoplasm of uncertain malignant potential proposed by the Milan System for Reporting Salivary Gland Cytopathology. Issue 7 (18th April 2018) - Liu, Haiyan; Ljungren, Clarissa; Lin, Fan; Zarka, Matthew A.; Chen, Longwen
Abstract : BACKGROUND: The Milan System for Reporting Salivary Gland Cytopathology is a tiered classification scheme that includes 6 diagnostic categories. Neoplasm, which is 1 of the 6 proposed categories, consists of benign neoplasm and neoplasm of uncertain malignant potential (NUMP). NUMP is reserved for a salivary gland neoplasm without clear distinction between benign and malignant. The objective of this study was to assess the risk of malignancy (ROM) of NUMP. METHODS: A retrospective analysis was conducted on 656 salivary gland fine‐needle aspiration specimens from 2010 to 2016. Cases that qualified as NUMP and had follow‐up surgical resections were reviewed and reclassified into basaloid neoplasm (BN) and salivary gland neoplasm with predominant oncocytic cell (SGNOC) groups. The ROM for each group was calculated. Fifty‐four salivary gland fine‐needle aspirations of NUMP that had surgical follow‐up were identified, which included 29 BNs and 25 SGNOCs. RESULTS: Histologic follow‐up for the BN group identified 14 cellular pleomorphic adenomas, 5 basal cell adenomas, 2 benign cystadenomas, 3 adenoid cystic carcinomas, 3 epithelial and myoepithelial carcinomas, 1 basal cell adenocarcinoma, and 1 myoepithelial carcinoma. Histologic follow‐up for the SGNOC group revealed 7 nodular oncocytoses, 6 Warthin tumors, 5 oncocytomas, 1 sebaceous adenoma, 1 mucinous cystadenoma, 2 acinic cell carcinomas, 2 mucoepidermoid carcinomas, and 1 mammary analog secretory carcinoma. The ROM was calculated at 24.1% for the NUMP category overall (27.6% for BNs and 20.0% for SGNOCs). CONCLUSIONS: The ROM of the SGNOC group is similar to that of the BN group but lower than the ROM (35%) proposed by the Milan system. Cancer Cytopathol 2018. © 2018 American Cancer Society. Abstract : Data from this study indicate that the risk of malignancy of the salivary gland neoplasm of uncertain malignant potential (24.1%) is lower than what is proposed by the Milan System for Reporting Salivary Gland Pathology (35%).